2012
DOI: 10.1590/s1519-99402012000200005
|View full text |Cite
|
Sign up to set email alerts
|

Taxa de deposição de tecidos corporais de novilhas Nelore e suas cruzas com Angus e Simental

Abstract: Objetivou-se avaliar a taxa de deposição de tecidos corporais de novilhas Nelore e suas cruzas com Angus e Simental. Foram utilizadas 57 novilhas de três grupos genéticos, das quais 19 eram do grupo Nelore, 19 Angus e 19 Simental, destas 12 (4 de cada grupo genético) foram abatidas no início do experimento (grupo referência) para estimativa da composição da carcaça dos demais animais. Outras 36 novilhas (12 animais de cada grupo genético) foram distribuídas em seis tratamentos, em esquema fatorial 3x2, de modo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
1
3
0
1
Order By: Relevance
“…In the evaluation of productive performance, the Guzerat animals exhibited initial weight, final weight and ADG values of 381.27, 497.20 and 1.45 kg, respectively, which were all lower than those obtained by the ½ Guzerat-Aberdeen Angus cattle (401.34, 541.34 and 1.75 kg, respectively). These findings agree with Souza et al (2012), who reported that crossbred animals were superior in productive performance; and Pitombo et al (2013), who stated that productive performance depends on factors such as breed, management and others.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In the evaluation of productive performance, the Guzerat animals exhibited initial weight, final weight and ADG values of 381.27, 497.20 and 1.45 kg, respectively, which were all lower than those obtained by the ½ Guzerat-Aberdeen Angus cattle (401.34, 541.34 and 1.75 kg, respectively). These findings agree with Souza et al (2012), who reported that crossbred animals were superior in productive performance; and Pitombo et al (2013), who stated that productive performance depends on factors such as breed, management and others.…”
Section: Resultssupporting
confidence: 91%
“…The most commonly observed behavioral changes in response to heat stress are increased water intake, decreased rumination, reduced feeding time, and increased time spent on other activities (Vilela et al, 2013). Souza et al (2012) stated that productive indices can vary according to the breed and cross used, which influence weight gain and carcass yields. Monitoring and evaluating the productive indices of a system allow the producer to identify the critical points, set resolutive goals and attain better results in less time.…”
Section: Introductionmentioning
confidence: 99%
“…Portanto, este fator pode interferir no aspecto comercial da carcaça, já que os cortes dessa região são menos valorizados, quando comparados aos cortes do quarto traseiro (cortes nobres da carcaça). Souza et al (2012) notaram diferenças entre grupos genéticos quanto a deposição de gordura subcutânea, sendo que o grupo de novilhas Angus apresentou maiores resultados que o grupo das raças Simental e Nelore. Isto ocorreu pelo fato de a raça Angus expressar a maturidade fisiológica primeiramente, uma vez que apresenta maior precocidade quando comparada as outras duas raças.…”
Section: Discussionunclassified
“…The weight gain rate has a direct impact on the degree of maturation of cattle and consequently on the composition of the gain; therefore, as the animal growth rate increases, the sooner it will achieve the plateau for muscle tissue deposition, exponentially increasing the adipose tissue deposition rate. Souza et al (2012) found an influence on the growth rate on the body composition of Zebu × Taurine crossbred cattle.…”
Section: Discussionmentioning
confidence: 90%